2018
DOI: 10.1590/1981-5344/2375
|View full text |Cite
|
Sign up to set email alerts
|

Analise bibliométrica 1990-2014: inteligência competitiva

Abstract: A inteligência competitiva (IC) fornece inteligência estratégica para a tomada de decisão, que proporciona vantagem competitiva nas empresas, porém, sem um processo adequado não é fácil desenvolver inteligência competitiva. O presente estudo tem o objetivo de identificar quais são os processos de IC existentes na literatura, concentrando-se na produção cientifica de proposta de modelos de IC. Pretende-se atingir este objetivo por meio de uma análise bibliométrica ao longo do tempo sobre IC para identificar e a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
2
0
1
Order By: Relevance
“…In relation to other bibliometric studies analysed, the findings of this manuscript coincide in the high diversity of concepts, disciplines, and approaches used to refer to competitive intelligence (Bergeron and Hiller 2002;López-Robles et al 2019a;López-Robles et al 2019b;Teixeira and Cristina 2017;Correia et al 2019;do Prado and Celso de 2018). Also, although the analysed manuscripts come from different sources and time periods (JISIB, Scopus, WoS, ABI/Inform, RBS), the most notable authors and journals in this subject are similar.…”
Section: Discussionsupporting
confidence: 68%
“…In relation to other bibliometric studies analysed, the findings of this manuscript coincide in the high diversity of concepts, disciplines, and approaches used to refer to competitive intelligence (Bergeron and Hiller 2002;López-Robles et al 2019a;López-Robles et al 2019b;Teixeira and Cristina 2017;Correia et al 2019;do Prado and Celso de 2018). Also, although the analysed manuscripts come from different sources and time periods (JISIB, Scopus, WoS, ABI/Inform, RBS), the most notable authors and journals in this subject are similar.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, we also applied the search string in Google Scholar to ensure research published on the subject was fully contemplated. The publication time was not limited, so it was possible for all published studies in this subject to have the same chance of being found (Do Prado and De Campos, 2018). Finally, we found 87 results in the Scopus database, 28 in Web of Science, 5 in Wiley, 7 in PubMed, and no articles were found in the Emerald database.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, we also applied the search string in the Google Scholar search engine to ensure research published on the subject was fully contemplated. No time period was defined for the articles, which made it possible for all previously published studies with the investigated theme to have the same chance of being found (do Prado and de Campos, 2018). The search returned 37 results in the Scopus database, 29 in Web of Science, 2 in Wiley, 11 in PubMed, and no articles were found in the Emerald database.…”
Section: Methodsmentioning
confidence: 99%